Assessment and Stabilization of the Critically Ill Patient - Joseph Turban (Association of American Medical Colleges, 2012)
Abstract This course is a simulation based resource, which emphasizes the use of the ABC method of stabilization and management of potentially critically ill patients. There is an initial PowerPoint slide show, outlining the concepts of utilizing the ABCs. This is followed by three simulation scenarios: status asthmaticus, unstable ventricular tachycardia, and acute congestive heart failure. The cases themselves were not meant to be a diagnostic challenge; rather, they are the vehicle with which the goals of the course, organizational progression through the steps of the ABC process, are emphasized. The first case, status asthmaticus, is a 16 year old with a previous history of hospital admission when much younger, who ran out of his inhalers several days ago and is now short of breath. On examination, his breath sounds are wheezes, but are barely audible. As he is treated, his wheezed become louder. One of the objectives is for the students to recognize the seriousness of the lack of wheezes, and that as they become louder indicate clinical improvement. The second case is unstable ventricular tachycardia (VT), requiring synchronized cardioversion. Objective include knowledge of the components that define stability in a potentially critically ill patient, and that for unstable VT with a pulse, the recommended therapy is synchronized cardioversion. As the course is written, if the students utilize synchronization, the patient converts to sinus rhythm, if synchronization is not used, the patient will convert on the third shock. This tests and encourages the students' adherence to details, and their conviction to the therapy. The third case of acute congestive heart failure (CHF) test the extent of the students knowledge of the management of CHF. The facilitator may ask questions such as causes, and different medication strategies. When the facilitator is satisfied, the scenarios shifts to several hours later, where the patient is now admitted to the floor, and is feeling much better, with improvements in dyspnea, tachypnea, physical exam findings and oxygen saturation. This course is effective in that it develops the lifelong skills of the approach to a critically ill patient, but also allows students the hands on advantage of managing a critically ill patient in a high fidelity simulation environment. When this course was presented as a component of a multi-day, simulation training event, which includes other simulation based courses, it consistently was ranked the highest and favorite portion of the event.